Nilai Religius dalam Cerita Rakyat Mbah Rogo Moyo di Kabupaten Kudus - Muzdalifah, Muzdalifah; Nabila, Mufthiri Silma; Aulia, Miftahul; Amelia, Nasywa Azka; Kanzunnudin, Mohammad (Edukhasi: Jurnal Inovasi Pendidikan, 2024)
The purpose of this research is to analyze the structure of Axel Olrix and the religious value contained in the story of Mbah Rogo Moyo. This research uses qualitative research methods. Regarding the source of data comes from a book entitled "Cerita Rakyat Pesisir Timur" written by Mohammad Kanzunnudin, published by CV Adhigama in 2024 page 81. The data is in the form of fragments of the Mbah Rogo Moyo story. Data collection techniques using reading and listening methods. The data analysis technique uses Miles and Huberman's theory, namely (1) data collection, (2) data reduction, (3) data presentation, (4) conclusion drawing. Based on the analysis of the story structure of Mbah Rogo Moyo, there are eight Axel Olrix structures and three religious values contained in the folklore of Mbah Rogo Moyo.